2018
DOI: 10.1007/s00408-018-0089-7
|View full text |Cite
|
Sign up to set email alerts
|

RV Fractional Area Change and TAPSE as Predictors of Severe Right Ventricular Dysfunction in Pulmonary Hypertension: A CMR Study

Abstract: The RVFAC is a good index to estimate RVEF in PH patients; even better than the TAPSE in patients with more severe hemodynamic profile, possibly for including the transversal component of right ventricular function in its measurement. Furthermore, RVFAC performance was similar in the two PH groups (PAH and CTEPH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 28 publications
5
32
1
Order By: Relevance
“…Our results are in concordance with previous studies on FWS echo and FAC echo/CMR [11,17] presenting a strong correlation with RVEF CMR with a modest correlation for TAPSE/AVPD lat and a weak correlation for S' echo compared to RVEF CMR [11,17]. As expected, the parameters measuring of area and volume change are closely related.…”
Section: Comparison With Rvef Cmrsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results are in concordance with previous studies on FWS echo and FAC echo/CMR [11,17] presenting a strong correlation with RVEF CMR with a modest correlation for TAPSE/AVPD lat and a weak correlation for S' echo compared to RVEF CMR [11,17]. As expected, the parameters measuring of area and volume change are closely related.…”
Section: Comparison With Rvef Cmrsupporting
confidence: 93%
“…As expected, the parameters measuring of area and volume change are closely related. In alignment with our study others have demonstrated a moderate correlation of RVEF CMR to AVPD lat [17] and FWS CMR [31,37]. The poor correlation between longitudinal measurements of RV function and RVEF CMR could be explained that RVEF is more related to fractional transverse movements than to longitudinal movements in patients with pulmonary hypertension [38].…”
Section: Comparison With Rvef Cmrsupporting
confidence: 90%
See 2 more Smart Citations
“…This results in a greater contribution of transverse contraction to global RV function as measured by changes in septal-to free-wall distance. 8,14,29,[32][33][34][35][36] In these cases, measures of longitudinal function will not reflect global RV function. Strain analysis supports these conclusions.…”
mentioning
confidence: 99%